Background
With the deepening of the heavy and inferior degree of crude oil, environmental regulations are increasingly strict, and the adoption of hydrogenation technology to treat residual oil can not only convert heavy oil into light oil products and improve the utilization rate of crude oil, but also reduce environmental pollution and meet the requirements of environmental regulations. Therefore, the residuum hydrotreating technology becomes the first technology for processing heavy oil by various refining enterprises.
Residuum hydrogenation techniques generally include fixed bed, moving bed, ebullated bed, slurry bed, and like process technologies. Among them, the fixed bed residuum hydrogenation technology has higher maturity and the most widely used. In fixed bed residuum hydroprocessing techniques, an upflow reactor (UFR) may be provided before the fixed bed reactor to extend the unit run length. In the upflow reactor, the mixture of the raw oil and the hydrogen flows upwards from the bottom of the reactor to pass through the catalyst bed layer, so that the whole catalyst bed layer is in a micro-expansion state, the pressure drop of the reactor is small, and meanwhile, impurity metals (mainly Ni and V), sulfur, nitrogen and the like in the raw oil can be effectively removed, the downstream fixed bed catalyst is protected, the performance of the whole catalyst is fully exerted, and the running period of the device is prolonged. It is generally believed that the upflow residuum hydrogenation catalyst is more suitable for smaller particle size spheres.
Most of the metal impurities in the residuum mainly exist in macromolecular compounds such as colloid, asphaltene and the like, the compounds have complex structures and large molecular sizes, and are difficult to diffuse in catalyst pore channels, so that the residuum hydrotreating process is a typical internal diffusion control process, and coke and removed metal are deposited on the surface of the catalyst and in the pore channels. In order to avoid rapid deactivation of the catalyst caused by plugging of deposited metal and coke in the pores of the catalyst surface, the upflow residuum hydrogenation catalyst is required to have an excellent pore structure, the catalyst surface layer of which should have macropores to satisfy diffusion and mass transfer of macromolecular compounds such as asphaltene, and the inside of which has a mesopore structure to provide a sufficient active surface, thereby improving the reactivity of the catalyst and prolonging the service life of the catalyst.
Patent CN 1665907A discloses an upflow hydrogenation catalyst, wherein a carrier of the catalyst consists of alumina, the pore volume is 0.6-1.1 mL/g, and the specific surface area is 110-190 m 2 And/g, wherein the pores with the diameter of more than 1000 angstroms are less than 35 percent, the peak pore diameter of the nitrogen desorption method is 80-140 angstroms, the shape of the catalyst is spherical or elliptical, and the granularity is about 0.1 inch (about 2.5 mm). The catalyst has smaller average pore diameter and is similar to the catalyst prepared by the U.S. Pat. No. 5472928Compared with the prior art, the catalyst has higher hydrodesulfurization activity and lower hydrodemetallization activity. In the hydrogenation of heavy oils, the heavy feedstock is contacted with a catalyst prepared according to US 5472928 under hydrodemetallization conditions, and the product is then hydrodesulfurized by contacting the catalyst. The catalyst is suitable as a hydrodesulfurization catalyst, and the service life of the catalyst can be prolonged only by the prior graded hydrodemetallization catalyst, so that the catalyst is not suitable for being singly used in an upflow reactor.
US patent 4448896 discloses an alumina carrier with smooth pore canal and its preparation method, which uses pseudo-boehmite as raw material and carbon black powder as pore-enlarging agent, and the alumina carrier is obtained by kneading, extruding, drying and roasting. The defect is that a small amount of carbon black powder is added, so that 'ink bottle' -shaped holes are easy to form, and smooth pore channels are difficult to form; too much carbon black powder can significantly reduce the carrier strength.
Patent CN 104646005a discloses a catalyst with an open "horn-shaped" pore structure and a preparation method, wherein the pore of the catalyst carrier is continuously enlarged from the center to the outer surface of the particle, and the average pore diameter is 19.0-30.0 nm. The method can alleviate the blocking problem of the catalyst orifice to a certain extent, but the catalyst surface layer lacks macropores, the improvement on the catalyst diffusion performance is limited, and macromolecular reaction substances such as asphaltene still have difficulty in penetrating into the center position of the catalyst particles.
Disclosure of Invention
Aiming at the defects of the prior art, the invention provides the step hole alumina and the preparation method thereof, the step hole alumina has the characteristics of large hole volume, large aperture and stepwise expansion of pore channels from inside to outside, and meanwhile, the surface layer of the step hole alumina contains a macroporous structure with a certain proportion of more than 100nm, so that the diffusion performance is excellent, and the step hole alumina can be used as a catalyst carrier, in particular to an up-flow type residual oil hydrotreating catalyst carrier.
In order to achieve the above purpose, the invention adopts the following technical scheme:
a spherical step hole alumina with a pore volume of 0.6-1.6 mL/g and a specific surface area of 80-250 m by mercury intrusion method 2 The average pore diameter is increased stepwise from the center to the outer surface along the radial direction of the sphere, wherein the average pore diameter from the center to 30-50% of the sphere radius from the center is 10-25 nm; the average pore diameter from the position of 30-50% of the sphere radius from the sphere center to the position of 50-80% of the sphere radius from the sphere center is 20-40 nm; the average pore diameter from the sphere radius of 50-80% from the sphere center to the outer surface of the sphere is 40-60 nm, and the outer surface of the sphere contains macropores with the diameter of more than 100nm, and the corresponding pore volume accounts for 20-60% of the total pore volume.
The preparation method of the spherical step hole alumina comprises the following steps:
(1) Uniformly mixing the pseudo-boehmite PB-1 with the molding auxiliary materials to obtain powder A, uniformly mixing the pseudo-boehmite PB-2 with the molding auxiliary materials to obtain powder B, and uniformly mixing the pseudo-boehmite PB-2 with the molding auxiliary materials and the template agent to obtain powder C;
(2) Conveying the powder A into a sugar coating machine, spraying a peptizing agent to form balls, and stopping conveying the powder A when the average particle size of wet balls reaches a proper size; then conveying the powder B into a sugar coating machine, continuously spraying a peptizing agent to carry out balling, and stopping conveying the powder B when the average particle size of wet balls reaches a proper size; then the powder C is conveyed into a sugar coating machine, a peptizing agent is continuously sprayed to carry out balling, and when the average grain diameter of wet balls reaches a proper size, the balling is finished;
(3) And (3) carrying out health maintenance, drying and roasting on the obtained wet spheres to obtain the spherical step hole alumina.
Further, the pseudo-boehmite PB-1 and PB-2 in the step (1) can be commercial products, and can also be products prepared by any method in the prior art, such as an aluminum sulfate method, a carbonization method, an aluminum alkoxide hydrolysis method, a hydrothermal method and the like.
Furthermore, the pore volume of the pseudo-boehmite PB-1 is 0.8-1.2 mL/g, and the specific surface area is 200-350 m 2 And/g, the grain size d (120) is 8-20 nm; the pore volume of the pseudo-boehmite PB-2 is 1.0-1.5 mL/g, and the specific surface area is 80-200 m 2 And/g, the grain size d (120) is more than or equal to 25 and nm.
Further, in the step (1), the molding auxiliary material is selected from one or more of sesbania powder, starch, methyl cellulose, polyacrylamide and polycarboxylic acid, and the addition amount of the molding auxiliary material is 0.3-5% of the dry basis weight of the corresponding pseudo-boehmite.
Further, the template agent in the step (1) is one or more of high polymer powder such as polyethylene, polypropylene, polyvinyl chloride, polystyrene and polyurethane, and the addition amount of the template agent is 5-30% of the mass of the pseudoboehmite PB-2 dry basis.
Further, the peptizing agent in the step (2) is various peptizing agents commonly used in the art, and may be aluminum sol and/or silica sol, or may be inorganic acid and/or organic acid solution, wherein the mass concentration of the inorganic acid and/or the organic acid is 2-20%, the inorganic acid may be one or several of nitric acid, phosphoric acid, hydrochloric acid and sulfuric acid, preferably nitric acid, and the organic acid may be one or several of oxalic acid, acetic acid and citric acid.
Further, the temperature of the health maintenance in the step (3) is 10-40 ℃ and the time is 6-48 hours.
Further, in the step (3), the drying temperature is 50-150 ℃ and the drying time is 1-24 hours.
Further, the roasting temperature in the step (3) is 600-1000 ℃ and the time is 1-6 h.
The obtained spherical step hole alumina can be used as a residual oil hydrogenation catalyst carrier, in particular to an up-flow residual oil hydrotreating catalyst carrier.
The invention has the remarkable advantages that:
the pore canal structure of the alumina obtained in the invention is distributed in a step-like manner, and the macroporous structure of the surface layer can meet the requirements of the diffusion and mass transfer of macromolecular compounds, reduce the occurrence of reaction on the surface layer and avoid the blockage of removed metal and carbon deposit on the orifice; the mesoporous structure with the larger middle layer can effectively promote the reaction process, so that metal and carbon deposit are deposited in the catalyst, and meanwhile, compound molecules which become smaller after the metal is removed are further diffused to the inner layer; the mesoporous structure with smaller inner layer has larger specific surface area, can provide enough places for reaction, and the reacted product molecules can be rapidly diffused out due to the macroporous structure of the outer layer. Therefore, the alumina prepared by the invention has excellent diffusion performance, and is particularly suitable for being used as an up-flow residual oil hydrotreating catalyst carrier.
The preparation method provided by the invention is simple, the process flow is short, the thickness of each layer can be flexibly adjusted and easily controlled, and the preparation method is easy to be applied to industrial practice.
Detailed Description
A spherical step hole alumina, the preparation of which comprises the steps of:
(1) Uniformly mixing the pseudo-boehmite PB-1 with the molding auxiliary materials to obtain powder A, uniformly mixing the pseudo-boehmite PB-2 with the molding auxiliary materials to obtain powder B, and uniformly mixing the pseudo-boehmite PB-2 with the molding auxiliary materials and the template agent to obtain powder C;
(2) Conveying the powder A into a sugar coating machine, spraying a peptizing agent to form balls, and stopping conveying the powder A when the average particle size of wet balls reaches a proper size; then conveying the powder B into a sugar coating machine, continuously spraying a peptizing agent to carry out balling, and stopping conveying the powder B when the average particle size of wet balls reaches a proper size; then the powder C is conveyed into a sugar coating machine, a peptizing agent is continuously sprayed to carry out balling, and when the average grain diameter of wet balls reaches a proper size, the balling is finished;
(3) And (3) carrying out curing for 6-48 hours at 10-40 ℃, drying for 1-24 hours at 50-150 ℃, and roasting for 1-6 hours at 600-1000 ℃ to obtain the spherical step hole alumina.
Wherein, the molding auxiliary materials in the step (1) are selected from one or more of sesbania powder, starch, methyl cellulose, polyacrylamide and polycarboxylic acid, and the addition amount of the molding auxiliary materials is 0.3-5% of the weight of the corresponding pseudo-boehmite dry basis. The template agent is one or more of high polymer powder such as polyethylene, polypropylene, polyvinyl chloride, polystyrene, polyurethane and the like, and the addition amount of the template agent is 5-30% of the mass of the pseudoboehmite PB-2 dry basis.
In order to make the contents of the present invention more easily understood, the technical scheme of the present invention will be further described with reference to the specific embodiments, but the present invention is not limited thereto.
Example 1
(1) 1000 g pseudo-boehmite PB-1 (pore volume of 1.0 mL/g, specific surface area of 220 m) was weighed 2 Mixing/g, crystal size d (120) of 15 nm) and 25 g sesbania powder uniformly to obtain powder A; 1000 g pseudo-boehmite PB-2 (pore volume of 1.2 mL/g, specific surface area of 120 m) was weighed 2 Mixing/g, crystal size d (120) 40 nm) and sesbania powder 25 g uniformly to obtain powder B; 1000 g pseudo-boehmite PB-2, 25 g sesbania powder and 70g polyethylene powder are weighed and mixed uniformly to obtain powder C1.
(2) Adding 20 g citric acid and 35 g nitric acid into 1000 g water, and stirring and mixing uniformly to obtain the peptizing agent P1.
(3) Conveying the powder A into a sugar coating machine, spraying a peptizing agent P1 to roll into balls, and stopping conveying the powder A when the average particle size of wet balls reaches 1.5 mm; then conveying the powder B into a sugar coating machine, continuously spraying a peptizer P1 to form balls, and stopping conveying the powder B when the average particle size of wet balls reaches 3.0 mm; and then the powder C1 is conveyed into a sugar coating machine and is continuously sprayed with a peptizer P1 for balling, and when the average grain diameter of wet balls reaches 4.0 mm, the balling is finished.
(4) The wet pellets were cured at room temperature 24 h, then dried at 80 ℃ for 6 h, and finally calcined at 650 ℃ for 4 h to give alumina sample S1.
Example 2
(1) 1000 g pseudo-boehmite PB-1 (pore volume of 1.0 mL/g, specific surface area of 220 m) was weighed 2 Mixing/g, crystal size d (120) of 15 nm) and 25 g sesbania powder uniformly to obtain powder A; 1000 g pseudo-boehmite PB-2 (pore volume of 1.2 mL/g, specific surface area of 120 m) was weighed 2 Mixing/g, crystal size d (120) 40 nm) and sesbania powder 25 g uniformly to obtain powder B; 1000 g pseudo-boehmite PB-2, 25 g sesbania powder and 80 g polyethylene powder are weighed and uniformly mixed to obtain powder C2.
(2) Adding 30 g citric acid and 35 g nitric acid into 980 g water, and stirring and mixing uniformly to obtain the peptizing agent P2.
(3) Conveying the powder A into a sugar coating machine, spraying a peptizing agent P2 for rolling to form balls, and stopping conveying the powder A when the average particle size of wet balls reaches 1.6 mm; then conveying the powder B into a sugar coating machine, continuously spraying a peptizing agent P2 for balling, and stopping conveying the powder B when the average grain diameter of wet balls reaches 2.8 mm; and then the powder C2 is conveyed into a sugar coating machine and is continuously sprayed with a peptizer P2 for balling, and when the average grain diameter of wet balls reaches 4.0 mm, the balling is finished.
(4) The wet pellets were left to stand at room temperature for 24 h, then dried at 80℃for 6 h, and finally calcined at 680℃for 4 h to give alumina sample S2.
Example 3
(1) 1000 g pseudo-boehmite PB-1 (pore volume of 1.0 mL/g, specific surface area of 220 m) was weighed 2 Mixing/g, crystal size d (120) of 15 nm) and 25 g sesbania powder uniformly to obtain powder A; 1000 g pseudo-boehmite PB-2 (pore volume of 1.2 mL/g, specific surface area of 120 m) was weighed 2 Mixing/g, crystal size d (120) 40 nm) and sesbania powder 25 g uniformly to obtain powder B; 1000 g pseudo-boehmite PB-2, 25 g sesbania powder and 90 g polyethylene powder are weighed and uniformly mixed to obtain powder C3.
(2) Adding 30 g citric acid and 40 g nitric acid into 980 g water, and stirring and mixing uniformly to obtain the peptizing agent P3.
(3) Conveying the powder A into a sugar coating machine, spraying a peptizing agent P3 to roll into balls, and stopping conveying the powder A when the average particle size of wet balls reaches 1.8 mm; then conveying the powder B into a sugar coating machine, continuously spraying a peptizing agent P3 for balling, and stopping conveying the powder B when the average grain diameter of wet balls reaches 3.2 mm; and then the powder C3 is conveyed into a sugar coating machine and is continuously sprayed with a peptizer P3 for balling, and when the average grain diameter of wet balls reaches 4.0 mm, the balling is finished.
(4) The wet pellets were left to stand at room temperature for 24 h, then dried at 80℃for 6 h, and finally calcined at 680℃for 4 h to give alumina sample S3.
Comparative example 1
(1) 1000 g pseudo-boehmite PB-1 (pore volume of 1.0 mL/g, specific surface area of 220 m) was weighed 2 /g, a crystal size d (120) of 15 nm) and 25 g sesbania powder,and mixing the materials uniformly to obtain powder A.
(2) Adding 20 g citric acid and 35 g nitric acid into 1000 g water, and stirring and mixing uniformly to obtain the peptizing agent P1.
(3) Powder A is conveyed into a sugar coating machine, a peptizer P1 is sprayed to roll into balls, and when the average grain diameter of wet balls reaches 4.0 mm, the balls are finished.
(4) The wet pellets were cured at room temperature for 24 h, then dried at 80℃for 6 h, and finally calcined at 650℃for 4 h to give alumina sample CS-1.
Comparative example 2
(1) 1000 g pseudo-boehmite PB-1 (pore volume of 1.0 mL/g, specific surface area of 220 m) was weighed 2 Mixing/g, crystal size d (120) of 15 nm) and 25 g sesbania powder uniformly to obtain powder A; 1000 g pseudo-boehmite PB-2 (pore volume of 1.2 mL/g, specific surface area of 120 m) was weighed 2 And/g, the crystal size d (120) is 40 nm) and 25 g sesbania powder are uniformly mixed to obtain powder B.
(2) Adding 20 g citric acid and 35 g nitric acid into 1000 g water, and stirring and mixing uniformly to obtain the peptizing agent P1.
(3) Conveying the powder A into a sugar coating machine, spraying a peptizing agent P1 for rolling to form balls, and stopping conveying the powder A when the average particle size of wet balls reaches 1.5 mm; then the powder B is conveyed into a sugar coating machine and is continuously sprayed with a peptizer P1 for balling, and when the average grain diameter of wet balls reaches 4.0 mm, the balling is finished.
(4) The wet pellets were cured at room temperature for 24 h, then dried at 80℃for 6 h, and finally calcined at 650℃for 4 h to give alumina sample CS-2.
1. The physicochemical properties of the aluminas obtained in the examples and comparative examples are shown in Table 1.
The method for measuring the average pore diameter of the alumina from the sphere center to different parts of the outer surface comprises the following steps: in the process of balling, when the spherical carrier grows to a certain particle size, taking out the sample, carrying out health preserving, drying and roasting, measuring the pore volume, the specific surface area and the average pore diameter of the sample by adopting a physical adsorption method, a mercury-pressing method and the like, and calculating the average pore diameter of different parts from the center of the sphere to the outer surface according to the relation that the total pore volume and the surface area of the sample are equal to the sum of all the parts.
Table 1 physicochemical properties of alumina samples obtained in examples and comparative examples
As can be seen from Table 1, the alumina prepared in the examples has an open pore structure with a stepped increase, and has a larger pore volume and pore diameter, and a considerable proportion of pore structures with a diameter of more than 100nm, wherein the pore diameter of the outer layer is obviously larger than that of the inner layer, and the pore is wider.
2. The alumina obtained in the examples and comparative examples was used as a carrier, and the same method was used to support the active metal, so that the corresponding catalysts all contained 5 wt% MoO 3 And 1 wt% NiO. The demetallization performance of the resulting catalyst was then evaluated on a 200 mL resid hydrogenation pilot plant. The sulfur content of the used raw material residual oil is 4.27 wt percent, the nitrogen content is 2870 ppm, the nickel content is 28 ppm, and the vanadium content is 85 ppm. The catalyst loading volume was 100 mL. The catalyst was presulfided by wet presulfiding prior to evaluation. The reaction conditions are as follows: the reaction temperature is 380 ℃, the hydrogen partial pressure is 15 MPa, and the liquid hourly space velocity is 1.0 h -1 The hydrogen oil volume ratio is 760. The process conditions for each catalyst were evaluated the same.
The content of nickel and vanadium in the oil before and after the reaction was determined by means of inductively coupled plasma emission spectrometry (ICP-OES) (see GB/T37160 for specific methods). The demetallization rate of each catalyst was calculated according to the following formula, and the evaluation results of the catalysts prepared from each alumina carrier are shown in table 2.
。
TABLE 2 determination of demetallization Rate of catalysts prepared with alumina from examples and comparative examples
The results in Table 2 show that the alumina supported catalyst prepared in the examples has higher demetallization activity and better activity stability.
The foregoing description is only of the preferred embodiments of the invention, and all changes and modifications that come within the meaning and range of equivalency of the claims are therefore intended to be embraced therein.